The Impact of Green Credit Policy on the Environmental Information Disclosure Level of "Two Highs and One Remaining" Enterprises: An Empirical Study Based on the PSM-DID Model - Li, Meilu (International Journal of Global Economics and Management, 2024)
To investigate the impact of green credit policy on the environmental information disclosure level of "two highs and one remaining" enterprises, this paper takes the issuance of the "Evaluation" in 2018 as a quasi-natural experiment, using data from A-share listed companies from 2010 to 2022 as samples, and employs the Propensity Score Matching-Difference-in-Differences (PSM-DID) method for empirical research. The results show that the implementation of the "Green Credit Guidelines" significantly improved the environmental information disclosure quality of "two highs and one remaining" enterprises, and the regional marketization level plays a positive moderating role in this process. This conclusion has been verified by parallel trend tests and placebo tests. Heterogeneity analysis indicates that compared to state-owned enterprises, the environmental information disclosure level of non-state-owned enterprises is more significantly promoted by green credit policy. This study provides important references and insights for the formulation and improvement of future green bond and other green financial policies by deeply exploring the impact and mechanism of green credit on corporate disclosure behavior.